2001
DOI: 10.1111/j.1447-0756.2001.tb01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Mediates Inhibitory Effect of Interleukin‐1β on Estrogen Production in Human Granulosa‐Luteal Cells

Abstract: IL-1beta stimulated NO production, and NO inhibited the production of estradiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In cultured human granulosa cells, IL-1β inhibited estradiol production and accelerated progesterone degradation [34,45]. Within the follicle of AL hens there is an increase in IL-1β protein and a decline in granulosa progesterone production and follicle wall MMP activities despite increased leukocyte infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…In cultured human granulosa cells, IL-1β inhibited estradiol production and accelerated progesterone degradation [34,45]. Within the follicle of AL hens there is an increase in IL-1β protein and a decline in granulosa progesterone production and follicle wall MMP activities despite increased leukocyte infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, IL-1 may have some effect on estradiol-17 production. It has been shown in vitro in human granulosa cells that IL-1 inhibits estradiol-17 production (Barak et al 1992), most probably by increasing NO production (Tobai & Nishiya 2001). IL-1 could also inhibit P450 aromatase activity (Yasuda et al 1990, Ghersevich et al 2001 as well as other enzymes involved in estradiol-17 synthesis (Hurwitz et al 1991, Ghersevich et al 2001.…”
Section: No Productionmentioning
confidence: 99%
“…However, in preterm birth, an increase in the levels of PGE2 in maternal serum and amniotic fluid has been documented in pregnant women with preterm birth 15 . Previous studies have demonstrated that in the inflammation state, expression of iNOS mRNA and NO production were also increased and secondary NO had pathophysiological affects 16–19 . Under pathophysiological conditions, high concentrations of NO can be either beneficial (e.g.…”
Section: Discussionmentioning
confidence: 99%